The Integration of Islamic Values and Local Wisdom in Rokat Pandhaba Tradition: A Living Hadith Study in Bagon Village, Jember - Peni Catur Renaningtyas; Miftahus Sa’diyah (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
The Rokat Pandhaba tradition is a hereditary cultural ritual practiced by the Pandhalungan community in Bagon Village, Jember Regency, East Java, Indonesia. Traditionally, the ritual is performed for children categorized as pandhaba as a means of seeking protection from misfortune, expressing gratitude to God, and praying for the child’s well-being and future prosperity. Despite its roots in local culture, the tradition has undergone a process of Islamization, resulting in a unique synthesis between Islamic teachings and indigenous cultural practices. This study aims to examine the implementation process of the Rokat Pandhaba tradition and to analyze the internalization of Islamic values embedded within its ritual practices through the perspective of Living Hadith. The study employed a qualitative phenomenological approach to explore the lived experiences, interpretations, and religious meanings attributed to the tradition by community members. Data were collected through in-depth interviews, participant observation, and documentation, and were analyzed using thematic analysis. The findings reveal that the implementation of Rokat Pandhaba consists of two interconnected stages: the siraman (ritual bathing) ceremony and the macapat or khataman event involving Qur’anic recitation, dhikr, and collective prayers. These ritual activities are guided by traditional practitioners, religious leaders, and community elders who play a crucial role in preserving local heritage while reinforcing Islamic norms. The study further demonstrates that Islamic values are internalized through symbolic ritual objects, Arabic prayers, Qur’anic recitations, charitable practices, and communal participation. Core values identified include tawhid (monotheism), gratitude, social solidarity, mutual cooperation, religious devotion, and communal harmony. From a Living Hadith perspective, the tradition illustrates how prophetic teachings are received, interpreted, and embodied in everyday cultural practices, enabling religious values to be transmitted across generations. The study concludes that Rokat Pandhaba serves not only as a mechanism for preserving local wisdom but also as an effective medium for religious education, moral formation, and the strengthening of Islamic identity within the Pandhalungan community.